2014
DOI: 10.2139/ssrn.2456123
|View full text |Cite
|
Sign up to set email alerts
|

The Weekend Effect: A Trading Robot and Fractional Integration Analysis

Abstract: This paper provides some new empirical evidence on the weekend effect, one of the most recognized anomalies in financial markets. Two different methods are used: (i) a trading robot approach to examine whether or not there is such an anomaly giving rise to exploitable profit opportunities by replicating the actions of traders; (ii) a fractional integration technique for the estimation of the (fractional) integration parameter d. The results suggest that trading strategies aimed at exploiting the weekend effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Agrawal and Tandon (1994) examined 19 equity markets around the world, and found the "day of the week" effect in most developed markets. Further evidence was provided by Olson et al (2011), Racicot (2011), Singal and Tayal (2014, and Caporale et al (2014), who found some evidence of a weekend effect in the US stock market, FOREX, and commodity markets as well as in the Russian stock market; in particular, fractional integration techniques suggest that the lowest orders of integration occur on Mondays.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Agrawal and Tandon (1994) examined 19 equity markets around the world, and found the "day of the week" effect in most developed markets. Further evidence was provided by Olson et al (2011), Racicot (2011), Singal and Tayal (2014, and Caporale et al (2014), who found some evidence of a weekend effect in the US stock market, FOREX, and commodity markets as well as in the Russian stock market; in particular, fractional integration techniques suggest that the lowest orders of integration occur on Mondays.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Further, Caporale et al (2014) show that this anomaly cannot be exploited to make abnormal profits (and therefore it is not inconsistent with the EMH) by taking a trading robot approach.…”
Section: Literature Reviewmentioning
confidence: 95%